Eco Friendly HRM: A Catalyst for Environmental Excellence in Hospitality - Jusdijachlan, Jusdijachlan; Susan Ridwan (International Journal of Advanced Multidisciplinary, 2023)
This article looks at components of human resource management (GRHM) practices to promote greater environmental performance with the goal of providing empirical proof that green HRM adoption is a key contributor to environmental performance in the hospitality industry. As a result, the part that follows summarizes the research findings and examines the literature review on GRHM practices, environmental performance, and underlying ideas. The researcher presents the research''s methodologies, findings, analysis, and conclusion in the next part.This research strategy combines literary (document) study with a qualitative methodology. The majority of local and international textbooks, papers, periodicals, sessions, websites, and electronic information, rules, laws, and regulations were employed by researchers to gather the data for this study. Google Schoolar was used to do journal searches. based on the search results discovered and choosing information that satisfies the requirements. The researcher used a systematic literature review technique to analyze the data, which entails selecting, analyzing, and interpreting a variety of data pertinent to the research topic in order to meet the study''s goals (Kitchenham and Charters, 2007).The results of numerous research demonstrate the considerable and favorable benefits of green human resource management strategies on environmental performance. Green recruitment, green training, and green awards are examples of environmentally friendly human resource management strategies that can boost an organization''s environmental performance and provide it a competitive edge Environmental protection or creating opportunities for employees to participate in ecological consultation and problem-solving groups and actively communicate with hotel industry leaders regarding environmental activities. Green performance appraisal plays an important role in achieving environmental performance as this practice provides a strategy for evaluating employee performance against environment-related standards and includes unrelated factors regarding green progress in performance feedback discussions. Environmental performance appraisal is a process through which employees are encouraged to improve their professional skills in environmental issues, thereby helping to better achieve environmental performance goals and objectives.